Social justice and legal education - Ashford, Chris; McKeown, Paul, 1980- (Cambridge Scholars Publishing, 2018)
Recent years have seen social justice emerge as a powerful driver for work, both in law schools and the legal services sector. However, questions remain about how that term is understood and given meaning within the legal academy and beyond. This edited collection explores the meanings that have emerged and might subsequently be developed, together with a practical exploration of projects that have sought to bring the social justice agenda to life in law schools and in communities around the world. Over the course of eighteen chapters, this volume engages with a range of social justice and legal education themes, including clinical legal education, innocence projects, access to justice, cause lawyering, LGBTQ identities, and sustainability in law schools. In addition, it also explores themes of ethics and values in contemporary legal education in Africa, Australia, North America, and the UK--back cover.